Total Quality Management Practices In Inland Revenue Board And It's Relationship On Employees' Organizational Commitment - Gunasegaran, Muthusamy (2001)
The purpose of this study is to identify the degree of TQM practices being implemented in IRB and to identify the relationship between these practices and IRB employees' organizational commitment. This study also aims to find out the impact of four moderators namely, job category, length of service, TQM understanding and TQM training on the relationship of TQM practices with employees' organizational commitment. This is a case study conducted on employees' of Inland Revenue Board in the Cheras, Wilayah Persekutuan branch. Data collection was done through questionnaires and there were 186 respondents. The findings of the study reveal that only two of the practices namely, customer focus and continuous improvement are being implemented in this branch. The other four practices leadership, process management, cooperation and learning are still lacking in implementation. The results reveal that there is a significant positive relationship between four TQM practices namely, customer focus, continuous improvement, cooperation as well as process management and employees' organizational commitment. Finally, the findings show five impact of moderating factors on the relationship between TQM practices and employees' organizational commitment. These are the relationship with continuous improvement moderated by job category, process management moderated by job category as well as TQM understanding and cooperation moderated by TQM training as well as length of service. It is hoped that IRB will review their current TQM practices and steps must be taken to understand key issues that have hampered successful implementation.